SERUM BIOCHEMICAL VALUES FOR NILE TILAPIA (OREOCHROMIS NILOTICUS) CULTURED UNDER AN INTENSIVE SYSTEM - Crivelenti, Leandro Z. (2011)
The aim of the study was to evaluate the serum biochemical parameters of the Nile tilapia (Oreochromis niloticus), Thai Chitralada lineage, raised under an intensive pisciculture system and captured by the cast net technique. Blood samples from 40 individuals were obtained by caudal venopuncture. Mean body weight was 453 ± 52 g. The serum biochemical parameters evaluated were total protein, albumin, globulins, acid uric, creatinine, urea, calcium, inorganic phosphorus, Ca/P ratio, alkaline phosphatase, and magnesium. In general, the data showed similar parameters in comparison to those established for scale fish, exception of the acid uric.